ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT KUNJUNG ULANG PADA OBYEK WISATA PEMANDIAN AIR PANAS GUCI DI KABUPATEN TEGAL - Damayanti, Mailiza; Ferdinand, Augusty Tae (Diponegoro Journal of Management, 2015)
This study aims to analyze things that can affect willingness to revisitÂ  GUCI hotspring object in Tegal Regency. This study departs from an axisting research problem â€œhow to increase willingness to revisit in GUCI Hotspring Object?â€this study was conducted by testing the affect of product image, product quality and customer value to willingness to revisit, where product attractiveness is used as an intervening variable.This research method use purposive sampling technique 150 respondents who have traveled to GUCI Hotspring Object in Tegal Regency. For method of Analysis using quantitative and qualitative method by Structural Equation Modelling (SEM) of the amos 20.0. Data used is primary data by questionnaire with some of open and closed questions.The result of this research prove that three of hypothesis are accepted and 1 hypothesis is rejected. The hypothesis accepted are both product quality and costumer value affect positively and significant to product attractiveness; and product attractiveness affect positively and significant to willingness to revisit. And the hypothesis rejected is product image not significant but have a positive influence to willingness to revisit.